JUDUL ABSTRAK TIDAK TERCANTUM DALAM BAHASA INGGRIS - FATHIYUL FAHMI (NIM : 10213063),
Wormhole is a region where the spacetime is very curved so that it can connects two different universes. Wormhole is first hypothesized by Ludwig Flamm in 1916 and mathematically studied by Albert Einstein and Nathan Rosen in 1935. In 1988 Michael Morris dan Kip Thorne analyze matter in the wormholes and concludes that wormholes need the existence of exotic matter which violates energy conditions. We will analyze the weak energy condition of wormhole in one of modified gravity theory, the theory of gravitation with nonminimal derivative coupling. We conclude that Schwarzschild wormhole in nonminimal derivative coupling also need theexistence of exotic matter which violates weak energy condition.